Pengajian Berbasis TPQ (Taman Pendidikan Al-Quran) bagi Pendidikan Anak untuk Meningkatkan Potensi Desa Gambiran - Aufia Aisa; Moh Khoirul Anam; Nurul Hidayah; M.Dzikrul Hakim Al-Ghozali; Achmad Riyan Veri; M Iftakhur Rozaki; Robiatul Adawiyah; Dita Dwi Cahya Andani Andani (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
One of the efforts to increase the understanding of the people of Gambiran Village from a religious perspective is that the service program is holding a